CAPABILITIES APPROACH AND BOURDIEUIAN NOTIONS OF PEDAGOGY - Skourdoumbis, Andrew (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This project aims to explore how pedagogic capacity of teachers can be enhanced to address the issue of student underachievement including strategies beyond the classroom. The project will focus on classroom based teacher effectiveness research and inquiry, and its relevance to the development of public education policy: an Australian context. The research will identify distinctive features of teacher capability to generate a framework of teacher capabilities in the key curriculum areas of Literacy/Humanities, Numeracy/Mathematics and Science. Teachers will be asked to identify the extent of their exposure to and application of capability. The analysis will also identify central themes in participants' descriptions of pedagogue to understand practitioner conceptions of teaching practice in standards-based curriculum contexts. This involves identifying and marking out precise teacher capabilities, as alternatives to current reified ‘multivariate analyses'. The study also examines how and where schools and systems can take their planning and preparation beyond current standardized teacher effectiveness approaches towards specific capability-based opportunities for teaching practice to advance individual student learning.